2017
DOI: 10.1080/00028487.2017.1302993
|View full text |Cite
|
Sign up to set email alerts
|

Does Bioelectrical Impedance Analysis Accurately Estimate the Physiological Condition of Threatened and Endangered Desert Fish Species?

Abstract: Bioelectrical impedance analysis (BIA) is a nonlethal tool with which to estimate the physiological condition of animals that has potential value in research on endangered species. However, the effectiveness of BIA varies by species, the methodology continues to be refined, and incidental mortality rates are unknown. Under laboratory conditions we tested the value of using BIA in addition to morphological measurements such as total length and wet mass to estimate proximate composition (lipid, protein, ash, wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 44 publications
1
3
0
Order By: Relevance
“…On the other hand, it was observed (49) weak and non-significant correlations among PA, Rs and Xc and the components of body composition, reporting that the reason for the weak correlation is that the methodology of BIA was not able to detect alterations in body composition of fish. This fact corroborates the results of other authors (50) , in which the morphological measures estimated by BIA in fish that face threat of extinction in inhabiting deserted regions were redundant, demanding caution in the field evaluation, as it presents great sensitivity.…”
Section: Bia Assessment In Fishsupporting
confidence: 91%
“…On the other hand, it was observed (49) weak and non-significant correlations among PA, Rs and Xc and the components of body composition, reporting that the reason for the weak correlation is that the methodology of BIA was not able to detect alterations in body composition of fish. This fact corroborates the results of other authors (50) , in which the morphological measures estimated by BIA in fish that face threat of extinction in inhabiting deserted regions were redundant, demanding caution in the field evaluation, as it presents great sensitivity.…”
Section: Bia Assessment In Fishsupporting
confidence: 91%
“…In contrast, Dibble et al. () found that the addition of BIA values that were taken on juvenile Humpback Gila cypha , Bonytail G. elegans , and Roundtail G. robusta chub into models with length and weight did not greatly increase the coefficient of determination values. Predictive body composition models that use BIA may differ in their utility based on what species is being studied.…”
Section: Discussionmentioning
confidence: 94%
“…Nevertheless, we believe such morphometric indices are sufficient for predicting fat content in C. cognatus to a degree that likely suits the needs of most researchers. Although newer, sometimes promising, non-lethal methods for assessing fat content in fish have emerged [48,57,58], their apparent lack of adoption outside of studies examining their efficacy suggests that traditional methods are not going away anytime soon.…”
Section: Discussionmentioning
confidence: 99%